Behavioral and physiological responses of Umbonium vestiarium to temperature variation from cold-water discharge of H-OTEC system - Leng, Qingxue; Yusuff, Ferdaus Mohamat; Mohamed, Khairul Nizam; Zainordin, Nazatul Syadia; Hassan, Zafri; Thirugnana, Sathiabama T.; Sarip, Shamsul (Nature Research, 2025)
Umbonium vestiarium is a prevalent benthic species in many tropical regions and is highly sensitive to environmental changes. Investigating the effects of low temperatures on its behavior and physiology is critical for understanding the ecological and environmental consequences of cold-water discharges associated with the Hybrid Ocean Thermal Energy Conversion (H-OTEC) system. Although assessing the ecological impact of cooling emissions from H-OTEC system is important, research on this subject remains limited. This study examined live specimens of U. vestiarium collected from the coast of Port Dickson, Malaysia. The organisms were grouped and cultured at temperatures of 10 °C, 16 °C, 23 °C, and 28 °C, with 30 individuals in each group. Behavioral (feeding, clinging, spreading, hiding, and crawling) and physiological (Chl-a consumption rate, respiration rate, body temperature, and gut passage rate) observations were conducted on all specimens across these temperature conditions. The statistical analysis revealed that within the experimental temperature range, low temperatures had an inhibitory effect on the survival of U. vestiarium. At 10 °C, the snails exhibited early mortality and a low final survival rate. At 16 °C, the snails remained in a prolonged resting state, while at 23 °C, they displayed pronounced behaviors such as retraction, hiding, and clinging. The highest levels of behavioral and physiological activity were observed at 28 °C. Additionally, body temperature and respiration rate increased significantly with rising water temperatures, while gut passage time showed an inverse relationship. Except at 23 °C, chlorophyll-a (Chl-a) consumption rates also increased markedly with higher water temperatures. The results of this study demonstrated that temperature significantly influenced the survival, behavior, and physiological responses of U. vestiarium under controlled laboratory conditions.